A habitação popular oitocentista na cidade contemporânea - O caso portuense - Estratégias de intervenção para a sua requalificação - Pedro Manuel de Oliveira Santos (2016)
In the present thesis are suggested intervention strategies for the rehabilitation of two cases of popular housing, from the nineteenth century, in the city of Oporto, through the definition of its value - historical, as a symbol of the relationship between home and industrial development in the urban grid; cultural, for being responsible for part of the conservation of Oporto identity, its values and traditions; social, as a compact, economic and community housing. Gathering bibliography and cartography reference, this document checks the conditions and considerations inherent to the situation, precarious, within these typologies. In this context, given the financial and legal disabilities of the residents, issues were identified, calling into question the existence of these spaces in the city, not only for his deteriorated state, but as well the aggressive acquisition of property's for local housing. Thus, in this document, a traditional domestic space is integrated in a contemporary urban discourse, in which it tries to illustrate visions and strategies of bounding possibilities.